1993
DOI: 10.1111/j.1471-4159.1993.tb03301.x
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Tyrosine Hydroxylase in the Striatum of Newborn Piglets in Response to Hypocapnic Hypoxia

Abstract: The effect of graded hypoxia induced by hyperventilation on the activity of tyrosine hydroxylase was measured in vivo by microdialysis. Microdialysis probes were inserted into the striatum of newborn piglets and perfused with medium containing 3-hydroxybenzylhydrazine, an inhibitor of L-aromatic amino acid decarboxylase. The level of 3,4-dihydroxyphenylalanine (DOPA) measured in the effluent dialysate was then an index of tyrosine hydroxylase activity. The oxygen pressure in the veins and capillaries of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Piglet model studies played a key role in establishing hypothermia as a treatment for HIE 21 , and are used in neonatal resuscitation research 22 . Various groups have used piglet models when performing research within asphyxia and HIE, and studies include hypothermia 23 , alpha-melanocyte-stimulating hormone 24 , cardiac arrest 25 , tyrosine hydroxylase activity 26 , repeated hypoxic exposure 27 , NMDA receptor activity 14 , and near-infrared spectroscopy 28 . The piglet HIE model presented in this report is technically challenging to work with, as minor adjustments during the course of the procedure may result in either too mild or too severe brain injury 29,2 .…”
Section: Introductionmentioning
confidence: 99%
“…Piglet model studies played a key role in establishing hypothermia as a treatment for HIE 21 , and are used in neonatal resuscitation research 22 . Various groups have used piglet models when performing research within asphyxia and HIE, and studies include hypothermia 23 , alpha-melanocyte-stimulating hormone 24 , cardiac arrest 25 , tyrosine hydroxylase activity 26 , repeated hypoxic exposure 27 , NMDA receptor activity 14 , and near-infrared spectroscopy 28 . The piglet HIE model presented in this report is technically challenging to work with, as minor adjustments during the course of the procedure may result in either too mild or too severe brain injury 29,2 .…”
Section: Introductionmentioning
confidence: 99%
“…Unilateral striatal injection of 6-hydroxydopamine in rats increases specific activity of tyrosine hydroxylase locally but not in the contralateral striatum [37], as if it were a compensatory response to the local toxic injury within the striatum. Similarly, when newborn pigs were exposed to mild hypoxia, dopaminergic synthesis rose and continued to do so after cessation of hypoxia, to ~ 140% of baseline level [38], consistent with a compensatory response to the ischemic injury to the striatum. Thus, two types of acute striatal injuries lead to increased dopamine synthesis, suggesting the possibility of its role as an early contributor to disease.…”
Section: Dopamine Excess In Parkinson's Diseasementioning
confidence: 70%
“…Of course, these white matter echolucencies related to so-called "late-onset PVL" can not be associated with hypocarbia during the 1st day of life. In addition to clinical studies, normoxic or hypoxic hypocarbia has been demonstrated to augment neonatal cerebral injury in different animal species underlining the potentially deleterious effects of hypocarbia (17,18). Which conclusions can be drawn from the study by Dammann et al?…”
mentioning
confidence: 86%